Service Leadership, Organizational Culture and Personality Influence on Performance: Evidence from Private Universities in the City of Bekasi - Saing, Bungaran; Moeins, Anoesyirwan; Muharam, Hari (Journal of Industrial Engineering & Management Research, 2024)
The purpose of this research is to analyze the influence of servant leadership, organizational culture and personality on lecturer performance in the context of Bekasi City Private Universities by placing work motivation as a mediator in one fit model. This study fills the research gap, and requires repeated testing to assess the impact of leadership service, organizational culture and personality on lecturer performance from different points of view. The research tool used was a cross-sectional quantitative study with a questionnaire (survey) of 250 respondents for all Bekasi City Private University lecturers using the Structural Equation Model with a fit mediation approach to prove the role of context. This research provides empirical evidence that lecturer performance is influenced by servant leadership, organizational culture and personality with work motivation as a mediating fit. The results of this analysis include positive guidance, especially regarding the importance of the role of leaders in empowering and encouraging lecturers through active involvement with them, and the existence of positive organizational principles that improve higher education performance